Risk factors for distal stent graft-induced new entry following endovascular repair of type B aortic dissection - Li, Qing; Wang, Long-Fei; Ma, Wei-Guo; Xu, Shang-Dong; Zheng, Jun; Xing, Xiao-Yan; Huang, Lian-Jun; Sun, Li-Zhong (Journal of Thoracic Disease; Vol 7, No 11 (November 28, 2015): Journal of Thoracic Disease, 2015)
Background: Distal stent graft-induced new entry (DSINE) has been increasingly observed following thoracic endovascular aortic repair (TEVAR) for type B aortic dissection (TBAD). We seek to identify the risk factors for DSINE following TEVAR in patients with TBAD. Methods: Between January 2009 and January 2013, we performed TEVAR for 579 patients with TBAD. The clinical data were retrospectively analyzed with univariate and multivariate analyses to identify the risk factors for DSINE. Results: Two patients (0.3%) died after the initial TEVAR. Morbidity included spinal cord injury in 2 (0.3%), stroke in 3 (0.5%) and endoleak in 12 (2.1%) patients. Clinical and radiological follow-up was complete in 100% (577/577) averaging 47±16 months. Late death occurred in 6 patients. DSINE occurred in 39 patients (6.7%) at mean 22±17 months after the initial TEVAR, which was managed with re-TEVAR in 25 and medically in 14. At 33±18 months after DSINE, 11 of patients managed medically (11/14) and all patients managed with re-TEVAR (25/25) survived (P=0.048). Freedom from DSINE was 92.7% at 5 years (95% CI: 90.0-94.7%). Using tapered stent grafts with a proximal end 4-8 mm larger than the distal end, TEVAR performed in the acute phase (≤14 days from onset) was associated with a significantly lower incidence of DSINE than TEVAR performed in the chronic phase (4.3%, 7/185 vs. 13.9%, 15/108; P=0.003). Risk factors for DSINE were stent grafts less than 145 mm in length [odds ratio (OR) 2.268; 95% CI: 1.121-4.587; P=0.023] and TEVAR performed in the chronic phase (OR 1.935; 95% CI: 1.004-3.731; P=0.049). Conclusions: Our results show that TEVAR performed during the acute phase and using stent grafts longer than 145 mm could decrease the incidence of DSINE in patients with TBAD. Tapered stent grafts with a proximal end 4-8 mm larger than the distal end may be helpful in preventing DSINE after TEVAR performed in the acute phase than TEVAR performed in the chronic phase, due to the difference in mobility of the dissected flap. Expedite repeat TEVAR is recommended to improve the clinical prognosis for patients with DSINE.